Evaluasi Penerapan Model Pembelajaran Problem Based Learning terhadap Kemampuan Berpikir Kritis pada Mata Pelajaran IPAS Kelas IV SDN Mojosongo 3 Surakarta - M. Hafid Ryandita Adji; Feri Faila Sufa; Mukhlis Mustofa (Journal on Education, 2024)
The objective of this study is to examine the implementation of the Problem-Based Learning (PBL) model on critical thinking skills in the IPAS (Integrated Science and Social Studies) subject for Class IV at SDN Mojosongo 3 Surakarta during the 2023/2024 academic year. This research was conducted at SDN Mojosongo 3 Surakarta using qualitative descriptive research. The subjects of this research were the school principal, class V teacher, 6 class IV students. Data collection techniques in this research are through observation, interviews, documentation. This research uses the CIPP evaluation method. The CIPP model is an abbreviation for context evaluation, input evaluation, process evaluation, and product evaluation. The CIPP evaluation model is an evaluation approach that is oriented towards decision makers (decision centric evaluation structured approach) to provide assistance to administrators or decision making leaders. The conclusion from the observation results shows that the application of the Problem Based Learning (PBL) model in Natural and Social Sciences (IPAS) learning in class IV at SDN Mojosongo 3 Surakarta has a positive and significant influence on students' critical thinking abilities. Through the application of this model, students are able to demonstrate increased abilities at several stages of critical thinking, namely interpretation, analysis, drawing conclusions, explanation, reflection and self-regulation.